Transculturation and migration in the story “report for an academy”, of Franz Kafka (Quaestiones Disputatae: temas en debate, 2016)
This article analizes the way the processes of transculturation and migration come together in the story: report for an academy by Franz Kafka. This comes from the theoretical conceptions of Ángel Rama, Antonio Cornejo Polar y Néstor García Canclini. First an approach to the term transculturation is done as this is represented in the experiences of the main character story. Second, a theoretical approach to the term migration is done. An analysis of the way the character gets into the process is done. Finally, how the main character is settled down in a non dialectical change is analized which reconfigures his identity, whenever he does not loose his esscence but he is a product of change.
Keywords: identit; Kafka; migration; migrante subject; non- dialectic heterogeneity tranculturation